Analysis of the air system of the 2-floor electronics industry building PT. CI - Srihanto; Moch.Sugiri; Parman Sinaga; Prio Sejati (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
For urban areas and Jakarta's industrial sector, air freshener systems and air conditioners are becoming increasingly necessary. At the electronics-focused PT. CI Jakarta, the air conditioner cools the space. The goal of this research is to raise staff comfort levels and productivity levels in order to enhance output. Planning information and a cooling load analysis are needed in order to implement the cooling system in the industrial building. To determine how much AC (Air Conditioner) is required, it is important to analyze the calculation of the design of the AC (Air Conditioner) in the industrial room at PT. CI. The first step in the planning process is to identify the industrial building data, which includes the room's area and wall material as well as its contents. Analyze cooling load to calculate engine power. Choosing a cooling system and cooling. The cooling load analysis at the electronics industry building produced 712 kW of results, including a sensible load of 705.83 kW and a Latent load of 3.03 kW. The machine uses R134a as its refrigerant. 355.5 HP for the compressor. COP 2.77 is of a medium size. The central AC system was chosen as the cooling system